Sosialisasi Hak Cipta Bagi Perwakilan Seniman Aceh - Rahmah, Siti; Ramli, Chairiyan; Junarlis, Junarlis; Erdiana, Erdiana; Azhar, Azhar (Abdurrauf Journal of Community Service, 2025)
Copyright is an exclusive right that attaches automatically to the creator of a work based on the declarative principle. However, many artists, including in Aceh, lack an understanding of the importance of copyright protection, making them vulnerable to plagiarism, piracy, or illegal use that is financially and morally damaging. Therefore, socialization is needed to raise awareness and understanding of copyright and its registration procedures. This activity aims to provide Aceh Artist representatives with an understanding of copyright, its legal protection, and copyright registration procedures. Thus, artists can legally protect their works and utilize the economic and moral rights attached to their creations. The socialization was carried out with a service learning approach, actively involving participants through material presentations, interactive discussions, questions and answers, and case studies. The materials covered the definition of copyright, principles of legal protection, the role of the National Collective Management Institution (LMKN), and copyright registration procedures. Participants consisted of representatives of Aceh Artists who are members of the Aceh Artists Assembly (MaSA). This activity succeeded in increasing participants' understanding of the importance of copyright and its registration procedures. Participants showed high enthusiasm during the discussion and Q&A sessions, and provided positive feedback. However, the scope of participants was still limited, so there is a need to expand the reach of the socialization to artists in other regions in Aceh for greater impact. Abstrak: Hak cipta merupakan hak eksklusif yang melekat secara otomatis pada pencipta suatu karya berdasarkan prinsip deklaratif. Namun, masih banyak seniman, termasuk di Aceh, yang kurang memahami pentingnya perlindungan hak cipta, sehingga rentan terhadap plagiarisme, pembajakan, atau penggunaan ilegal yang merugikan secara finansial dan moral. Oleh karena itu, diperlukan sosialisasi untuk meningkatkan kesadaran dan pemahaman tentang hak cipta serta prosedur pendaftarannya. Kegiatan ini bertujuan untuk memberikan pemahaman kepada perwakilan Majelis Seniman Aceh (MaSA) mengenai hak cipta, perlindungan hukumnya, serta tata cara pendaftaran hak cipta. Dengan demikian, seniman dapat melindungi karya mereka secara hukum dan memanfaatkan hak ekonomi serta moral yang melekat pada ciptaan mereka. Sosialisasi dilaksanakan dengan pendekatan service learning, melibatkan peserta secara aktif melalui presentasi materi, diskusi interaktif, tanya jawab, dan studi kasus. Materi mencakup definisi hak cipta, prinsip perlindungan hukum, peran Lembaga Manajemen Kolektif Nasional (LMKN), serta prosedur pendaftaran hak cipta. Peserta terdiri dari perwakilan Seniman Aceh yang tergabung dalam Majelis Seniman Aceh (MaSA). Kegiatan ini berhasil meningkatkan pemahaman peserta tentang pentingnya hak cipta dan prosedur pendaftarannya. Peserta menunjukkan antusiasme tinggi selama sesi diskusi dan tanya jawab, serta memberikan umpan balik positif. Namun, cakupan peserta masih terbatas, sehingga diperlukan perluasan jangkauan sosialisasi ke seniman di wilayah lain di Aceh untuk dampak yang lebih luas. Kata Kunci: Hak Cipta, Seniman Aceh, Karya